Le recensement du patrimoine mobilier des églises de l’Aube - Xavier de Massary; Bruno Decrock (In Situ)
From 2002 to 2004, a team of researchers undertook a recording survey of all the furniture and furnishings in the churches of the Aube department, one of the richest in France in terms of its protected religious heritage. The operation was unprecedented in terms of rapidity and the means mobilised. It covered 551 buildings and led to the completion of 12,000 individual notices, using the electronic recording files developed by the services of the Inventaire général. The project was led by the heritage services of the department, with help from those of the region (DRAC Champagne-Ardenne), in particular the historic monuments service and the Inventaire général, this last giving guidance on the methodological aspects of the programme.